Algebraic generation of single domain computational grid for twin screw machines. Part I. Implementation. (May 2017) - Rane, Sham; Kovacevic, Ahmed
Highlights: New algebraic algorithm for deforming grid generation of twin screw machines developed. Regularized distribution achieved by control function and a reference blocking structure. Independent grid refinement in interlobe region achieved for better accuracy in the leakage gaps. Non-conformal interface between two rotor domains eliminated, thereby producing a single domain. New grid adaptable with multiple CFD flow solvers and capable of solving multiphase models. Abstract: Special attention is required for generation of computational grids in highly deforming working chambers of twin screw machines for 3D CFD calculations. Two approaches for customised grid generation are practically available. The first is an algebraic grid generation and the second is a differential decomposition method. This paper reports on new developments in the algebraic approach that has the advantages associated with both algebraic and differential methods. Two control functions are introduced for regularisation of the initial algebraic distribution. One is based on an analytical control function in transformed coordinate system while the other uses background blocking structure in order to guide the initial algebraic distribution towards a single computational mesh. This paper presents implementation and grid characteristics of these new functions. Developed grids have been tested and results from flow calculations on a dry air compressor have been validated in part II of the paper[29] . It was possible to achieve two distinct characteristics desirable in a twin screw rotor domain mesh. Firstly, it is possible to independently control grid refinement in the interlobe region thereby providing better accuracy in representation of the leakage gaps. Secondly and most importantly, it is possible now to eliminate the non-conformal interface between the two rotor domains thereby producing a single domain structured grid for the rotors, while still maintaining the fully hexahedral cell topology. An improvement in the global orthogonality of the cells was achieved. Despite of a decrement in the Face warp quality, aspect ratio of cells retained similar scale.